Transformasi Pendidikan Melalui Kurikulum Merdeka Belajar: Studi Tren Model Pembelajaran Di Sekolah Dan Madrasah - Imam Fatoni (PEDAGOGIA : JURNAL KEGURUAN DAN PENDIDIKAN, 2024)
The transformation of education in Indonesia through the implementation of Merdeka Belajar Curriculum has encouraged the implementation of various innovative learning models in schools and madrasah. This research aims to analyse the effectiveness and challenges of implementing Inquiry Learning, Problem-Based Learning, Project-Based Learning, Blended Learning, and Flipped Classroom learning models in improving learning quality and students' 21st century skills. This research uses a qualitative approach with a case study method. Data sources were obtained through in-depth interviews with 30 educators in schools and madrasahs, classroom observations, and analysis of education policy documents. The results show that the implemented learning models are able to increase student engagement, critical thinking, creativity, and collaboration in learning. Blended Learning and Flipped Classroom models received positive responses regarding flexibility and accessibility, although there are still obstacles in digital infrastructure readiness. Meanwhile, the Problem-Based Learning and Project-Based Learning models proved effective in building students' problem-solving and cooperation skills